Surgically treated supratentorial gliomas in the adult. Favourable action of a podophyllin derivative (VM 26) administered alone (author's transl) - Trouillas, P; Chassard, J L; Tommasi, M; Aimard, G; Devic, M (La Nouvelle presse medicale, 1978)
The action of VM 26 on cerebral glioblastomas was suggested by studies of phase II or protocols in which the drug was used in association. The randomised protocol presented here, involving 10 treated subjects and 11 controls, showed that VM 26 was active in terms of the duration of survival of patients undergoing surgery for a glioblastoma. The mean survival was 16.4 months as against 9.6 months in the controls (statistically significant difference at p less than 0.05). This activity would tend to characterise the drug as one of the essential factors in the chemotherapy of all malignant gliomas, in particular since it is itself free of all haematological complications, even at high doses, and causes scarcely any allergic problems.